Adsorption studies of heavy metal solutions using corn cobs adsorbents - Lim Hooi Peng (School of Environmental Engineering, University Malaysia Perlis, 2012)
In this study, corn cobs were utilized as an adsorbent to remove heavy metals (Cu and Zn) from aqueous solution. The influences of initial Cu (II) and Zn (II) ion concentration (25 - 200 ppm) with contact time, temperature (303K, 313K and 323K) and pH (2 - 6) have been investigated. Experimental tests were conducted in a batch process and percentage of metal ions removal was analyzed by using Atomic Absorption Spectrometer (AAS) with dosage 0.6g and 100mL of metal solution. The adsorption studies were represented by Isotherm, Kinetic and Thermodynamic analysis. Scanning Electron Microscopy (SEM) was used to examine surface morphology and functional group of surface was conducted by using FT-IR techniques. Maximum percentage of metal ions removal for untreated corn cobs with copper achieved 80.95% at 323K and 39.8% for zinc at303K. For treated corn cobs with copper achieved at 58.64% at 323K and 20.8% at 303K for zinc. From isotherm studies, untreated corn cob applied for heterogeneous surface and multilayer sorption, while treated corn is applied to homogeneous surface and monolayer adsorption. Kinetic studies depicted that pseudo second order is better than pseudo first order. Thermodynamic depicted adsorption is non-spontaneous and undergo endothermic with irreversible process.